Long COVID and its effects on the cardiovascular system: a literature review - Itua, Blessing; Chukwuka, Columba (International Journal of Research in Medical Sciences, 2022)
A significant cardiac burden exists post COVID-19. This is evident by persistent chest pain, palpitations, dyspnea, exertional fatigue, presence of new-onset heart failure or arrhythmia. Persistent COVID-19 symptoms in the cardiovascular system may be caused by a combination of processes that either increase inflammation or tamper with the autonomic nervous system. The inflammation can be caused by viral load persistence leading to tissue damage. The presence of cytokines and chemokines results in a state of hyper inflammation, immune exhaustion, organ damage during the infectious state and post-viral autoimmunity. The current review aims to discuss the risk factors, pathophysiology and treatment of the protracted form of COVID-19 in relation to the cardiovascular system.